T1 Hypoxia-Inducible Factor 2α Regulates Neutrophilic Inflammation in Humans, Mice and Zebrafish. (19th November 2012) - Thompson, AAR; Elks, PM; Marriott, HM; Higgins, KR; Parmar, S; Shaw, G; Eamsamarng, S; McGrath, EE; Formenti, F; Eeden, FJ Van; Kinnula, VL; Pugh, CW; et al.
Abstract : Neutrophilic inflammation plays an important role in inflammatory lung diseases but therapeutic targeting of neutrophil (PMN) persistence is lacking. PMN lifespan and function is regulated by hypoxia, a characteristic feature of inflamed tissues, via the HIF/VHL/hydroxylase pathway, specifically hypoxia inducible factor-1α (HIF-1α) and prolyl hydroxylase-3 (PHD3). Targeting HIF-1α in myeloid cells impaired immune function, but PHD3 regulated PMN lifespan without affecting function. Given that PHD3 preferentially regulates HIF-2α, we investigated the role of HIF-2α in PMN-mediated inflammation. Peripheral blood PMNs isolated from healthy volunteers and mice expressed HIF-2α and expression was enhanced by heat-killed bacteria. Using PMNs isolated from patients with active inflammatory arthritis (IA) we demonstrated significant upregulation of HIF2A mRNA (IA 92.9±30.3 vs. control 4.3±0.9 AU relative to ACTB, P <0.05) and protein (IA 0.26±0.05 vs. control 0.01±0.01 OD relative to P38, P <0.01) in circulating inflammatory PMNs. PMNs recruited to the airways of patients with COPD also displayed strong HIF-2α staining. The consequences of HIF-2α upregulation were examined using human PMNs from patients with gain-of-function mutations in the HIF2A gene. Neutrophils isolated from these patients had reduced rates of constitutive apoptosis. Recapitulation of the human HIF2A mutations in the orthologous HIF2A gene, epas1a, in zebrafish delayed resolution of inflammation in a tail injury model (24 hrs post injury, epas1a 12.7±1.4 vs. ctrl 5.2±0.5 PMNs, p<0.001) with an associated reduction in PMN apoptosis ( epas1a 1.0% vs. ctrl 1.6%, p<0.05). Mice with myeloid-specific deletion of Hif2a had normal PMN survival in response to hypoxia and the cells showed no functional defect in vitro . Importantly, in a PMN-mediated acute lung injury model, myeloid-specific deficiency of HIF-2α markedly enhanced resolution of inflammation (BAL PMN count 48 hours following nebulised LPS, WT 2.13×10 6 ±0.08 vs. KO 1.39×10 6 ±0.24, p<0.05) and reduced lung injury (BAL IgM at 48 hours, WT 211±22.8 vs. KO 74.7±27.2 ng/ml), implicating HIF-2α in PMN persistence in inflamed lung tissue. These data support a critical and selective role for HIF-2α in the resolution of inflammation through the maintenance of PMN survival, and provide a platform to dissect the therapeutic utility of targeting HIF-2α in chronic inflammatory diseases.